Forecasting the Impact of the Soon to be Traded Stock Index Futures on the Chinese Stock Market: Empirical Evidence from Japan and Taiwan - Wang, Xuewen (2007)
China will launch the stock index futures in the later of 2007. This paper forecasts the impact of stock index futures on the volatility of the Chinese stock market based on the empirical test of Japan and Taiwan. The GARCH model will be used to examine on the effect of stock index futures on the volatility of the spot market. The forecasts will be made based on analysing the Japanese and Taiwanese stock market. However, the forecasts are suggestive not conclusive. The further studies are needed based on Chinese data. The importance of stock index futures on the Chinese stock market and the impact of SGX FTSE Xinhua A 50 stock index futures on the volatility of the Chinese stock market will also be discussed.